Anomalous thickness-dependent exchange bias effect in Fe3O4/YMnO3 multiferroic heterostructures. (5th May 2015) - Zheng, Dongxing; Sun, Mingyu; Li, Dong; Li, Peng; Jin, Chao; Bai, Haili
Abstract: Full-oxide epitaxial heterostructures consisting of multiferroic hexagonal YMnO3 and ferromagnetic Fe3 O4 with variable thicknesses were fabricated by magnetron sputtering. A parabolic-like exchange bias (EB) effect varying with the thickness of Fe3 O4 was discovered, while the EB effect in Fe/YMnO3 and Fe3 O4 /BiFeO3 heterostructures follows a reciprocal relation (, where is the thickness of FM layer). The parabolic-like EB effect is considered to be associated with the joint effect from the special uncompensated moment at the antiferromagnetic domain walls in YMnO3 and the interactions among antiphase domains (APDs) in Fe3 O4 . By changing, the strength of the interaction among APDs can be modulated, giving rise to the anomalous thickness-dependent EB effect.